2018
DOI: 10.1128/msphere.00223-18
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Like Nylon-3 Polymers with Activity against Phylogenetically Diverse, Intrinsically Drug-Resistant Pathogenic Fungi

Abstract: Fungi reside in all ecosystems on earth and impart both positive and negative effects on human, plant, and animal health. Fungal disease is on the rise worldwide, and there is a critical need for more effective and less toxic antifungal agents. Nylon-3 polymers are short, sequence random, poly-β-amino acid materials that can be designed to manifest antimicrobial properties. Here, we describe three nylon-3 polymers with potent activity against the most phylogenetically diverse set of fungi evaluated thus far in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Nylon-3 copolymers or poly-β-peptides are a family of synthetic peptide-like polymers based on the structural moiety of AMPs and are made via anionic ring-opening polymerisation of β-lactams (Yang et al, 2011). The resulting polymers (MM-TM, DM-TM, and NM) display improved potency against a diverse range of fungal species including C. albicans, C. krusei, C. auris, C. neoformans, C. amylolentus and A. fumigatus with improved fungal selectivity over mammalian cells (Liu et al, 2013;Liu et al, 2014;Rank et al, 2018). The most effective nylon-3 polymer was found to be poly-βNM, composed of the cationic subunit βNM and the hydrophobic subunit CH in differing proportions.…”
Section: Synthetic Antimicrobial Peptide-like Polymers With Antifungal Activitymentioning
confidence: 99%
“…Nylon-3 copolymers or poly-β-peptides are a family of synthetic peptide-like polymers based on the structural moiety of AMPs and are made via anionic ring-opening polymerisation of β-lactams (Yang et al, 2011). The resulting polymers (MM-TM, DM-TM, and NM) display improved potency against a diverse range of fungal species including C. albicans, C. krusei, C. auris, C. neoformans, C. amylolentus and A. fumigatus with improved fungal selectivity over mammalian cells (Liu et al, 2013;Liu et al, 2014;Rank et al, 2018). The most effective nylon-3 polymer was found to be poly-βNM, composed of the cationic subunit βNM and the hydrophobic subunit CH in differing proportions.…”
Section: Synthetic Antimicrobial Peptide-like Polymers With Antifungal Activitymentioning
confidence: 99%
“…Nylon-3 polymers have been proven to have significant activity against pathogenic strains of C. albicans that are resistant to conventional medication. Particularly, nylon-3 polymers with β-amino residues (βNM) in their backbone structure attracted more interest due to their resemblance to proteins that induce biocompatibility [60][61][62][63]. Moreover, such nylon-3 polymers can be easily prepared, being promising as clinical antifungal agents [60].…”
Section: Polymeric Materialsmentioning
confidence: 99%
“…From these pioneering works, more studies emerged in which different nylon-3 derived copolymers were studied. On one of these studies, the evaluated nylon-3 derivative showed excellent antifungal activity against several organisms from the genera Candida and Cryptococcus, comparable to fluconazole and amphotericin B (AmB) (Rank et al, 2017(Rank et al, , 2018, even showing synergism when used along these antifungals. Unfortunately, these substrates were not effective against Aspergillus spp by themselves, but they were shown to enhance the effect of other azole antifungals such as posaconazole and itraconazole against these pathogens.…”
Section: A Final Series Of Examples Of Chitosan Modification Is the Workmentioning
confidence: 99%
“…Finally, for this work, the cytotoxicity of the compounds was evaluated and it was concluded that these compounds are still biocompatible up to doses much higher than the determined MICs (Rank et al, 2017). In a follow-up study, the same research group evaluated new derivatives of these compounds obtaining an extensive list of inhibition interactions within several genera of fungi (Rank et al, 2018).…”
Section: A Final Series Of Examples Of Chitosan Modification Is the Workmentioning
confidence: 99%